Prosedur Pembayaran Booth pada event Indonesia International Hospital Expo 2018 divisi finance PT Okta Sejahtera Insani - Endah Retno Nawang Wulan; Dewi Winarni Susyanti (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2020)
This research aims to find out how the booth payment procedure at the Indonesia International Hospital Expo 2018. The research method used by the author is a qualitative method accumulation of observation and interviews in finance division team and leader of Indonesia International Hospital Expo 2018. From the results of the research with using the method, the authors obtain the results of research that the booth payment procedure at the Indonesia International Hospital Expo 2018 is arranged to high up efficiency in service provider activities as PEO (Professional Exhibition Organizer) to exhibitors.